2007
DOI: 10.1086/511023
|View full text |Cite
|
Sign up to set email alerts
|

Microlensing of a Biconical Broad‐Line Region

Abstract: The influence of microlensing in the profiles of the emission lines generated in a biconical geometry is discussed. Microlensing amplification in this anisotropic model is not directly related to the bicone's intrinsic size but depends on the orientation of the bicone axis and on the cone aperture. The orientation of the projected bicone with respect to the shear of the magnification pattern can induce very interesting effects, like the quasi-periodic enhancements of the red/blue part of the emission line prof… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…Only one other system (HE 0047-1756) shows ML similar to the one observed in SDSS J0246-0825 but with a larger signal in one wing than in the other, a case which should in principle be more likely (Abajas et al 2002(Abajas et al , 2007. This might be an observational bias (microlensing of the other wing is too small to be detected), or not.…”
Section: Consequences For the Blrmentioning
confidence: 68%
See 1 more Smart Citation
“…Only one other system (HE 0047-1756) shows ML similar to the one observed in SDSS J0246-0825 but with a larger signal in one wing than in the other, a case which should in principle be more likely (Abajas et al 2002(Abajas et al , 2007. This might be an observational bias (microlensing of the other wing is too small to be detected), or not.…”
Section: Consequences For the Blrmentioning
confidence: 68%
“…This effect is expected for most of the BLR geometries studied in the literature when the source lies in a large demagnification valley of the micro-caustic network or when a large fraction of the source crosses a micro-caustic (e.g. Abajas et al 2007). In the first case the symmetry should last several crossing timescale 7 while in the second case, the effect should be more transient.…”
Section: Microlensing Of the Blrmentioning
confidence: 87%
“…The BLR was once considered too large to be affected significantly by microlensing. Studies have shown, however, that the BLR can be small enough to be amplified significantly by stellar-mass objects (Abajas et al 2007, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…In a more detailed investigation, Lewis et al [48] showed that spectroscopic monitoring of multiple quasars can be used to probe the broad line regions (cf. also [1,2,9,49,51,71]). …”
Section: Theoretical Work On Quasar Microlensingmentioning
confidence: 97%